SAT0007 Fine-mapping of the 5Q31 psoriatic arthritis susceptibility LOCI in a british population. (23rd January 2014) - Bluett, J.; Bowes, J.; Ho, P.; Korendowych, E.; McHugh, N.; Packham, J.; Bruce, I.N.; Barton, A.
Abstract : Background: Psoriatic Arthritis (PsA) is a chronic inflammatory arthritis associated with psoriasis which manifests as a heterogeneous disease with a wide spectrum of disease severity. PsA is a complex disease whereby environmental factors trigger disease in genetically susceptible individuals and multiple genetic factors contribute towards disease susceptibility. The overlap of PsA with psoriasis has resulted in confounding results for genome wide association studies (GWAS) producing difficulty in separating out the 2 diseases. There is however evidence from subgroup analysis of a GWAS to suggest that a locus on chromosome 5q31 is specifically associated with PsA (1). This result has been replicated in two independent studies involving UK and Canadian subjects (2, 3). There is substantial linkage disequilibrium within this locus necessitating the need for fine mapping within the region. Objectives: To fine-map the chromosome 5q31 region using a dense set of single nucleotide polymorphisms (SNPs) to refine the association signal to a specific gene or regulatory element. Methods: Genotype data for a total of 1518 SNPs spanning the 5q31 region (131.4-132.2Mb) was available for 929 PsA UK cases and 4537 UK healthy controls (www.wtccc.org.uk ). Genotyping was performed as part of a wider study targeting confirmed autoimmune susceptibility loci using the Immunochip Illumina iSelect array. A strict quality control (QC) process was applied to the dataset followed by single point analysis using the Armitage test for trend. Results: Following stringent QC, the analysis of 1440 high quality SNPs in 862 cases and 4306 controls identified an association to rs715285 (p=8.92×10 -5 ). This localises the association to an intergenic region flanked by the genes: colony stimulating factor 2 ( CSF ) and prolyl 4-hydroxylase, alpha polpeptide II ( P4HA2 ). Conclusions: This preliminary analysis localises the association signal for susceptibility to PsA to an intergenic region approximately 500Kb away from the previously identified IL13 SNP (rs20541), demonstrating the importance of fine-mapping. The study highlights two genes for consideration in disease aetiology: the cytokine CSF2 and P4HA2 which encodes a subunit of the proly 4-hydroxylase; a key enzyme involved in collagen synthesis. References: Duffin KC, Freeny IC, Schrodi SJ, Wong B, Feng B-J, Soltani-Arabshahi R, et al. Association between IL13 polymorphisms and psoriatic arthritis is modified by smoking. Journal of Investigative Dermatology. [Research Support, N.I.H., Extramural Research Support, Non-U.S. Gov't]. 2009 Dec;129(12):2777-83. Bowes J, Eyre S, Flynn E, Ho P, Salah S, Warren RB, et al. Evidence to support IL-13 as a risk locus for psoriatic arthritis but not psoriasis vulgaris. Annals of the Rheumatic Diseases. 2011 June 1, 2011;70(6):1016-9. Eder L, Chandran V, Pellett F, Pollock R, Shanmugarajah S, Rosen CF, et al. IL13 gene polymorphism is a marker for psoriatic arthritis among psoriasis patients. Annals of the Rheumatic Diseases. [Multicenter Study Research Support, Non-U.S. Gov't]. 2011 Sep;70(9):1594-8. Disclosure of Interest: None Declared